Colloidal synthesis of copper cadmium sulphide (CuCdS2) nanoparticles and its structural, optical and morphological properties. (1st August 2017) - Saravanan, K.; Suriakarthick, R.; Ananthakumar, S.; Babu, S. Moorthy; Selladurai, S.
Abstract: Oleylamine mediated CuCdS2 nanoparticles were synthesized by the colloidal hot injection method at 230 °C. Structural analysis reveals that the nanoparticles exhibit wurtzite phase with high crystallinity. The average crystallite size of the nanoparticles was calculated as 40 nm. Optical band gap of the synthesized nanoparticles was calculated from UV-vis absorption spectrum as 1.70 eV. Nanorods and nanoplates like morphologies with well-defined boundaries of CuCdS2 nanoparticles were observed from scanning electron microscope analysis. Purity of the synthesized nanoparticles was confirmed using energy dispersive X-ray analysis. Vibrational modes of CuCdS2 nanoparticles were observed from the Raman spectroscopy analysis. X-ray photon spectroscopy analysis confirms the oxidation states of the elements present in the nanoparticles. The possible mechanism involved in the formation and morphology of CuCdS2 nanoparticles was discussed.